The role of ICT in shaping international trade dynamics: a G20 perspective - Park, Noori; Choi, Chang Hwan (Technological and Economic Development of Economy, 2025)
This research examines the influence of Information and Communication Technology (ICT) on economic expansion and commerce within G20 nations. Findings reveal that the digital revolution and advancements in artificial intelligence have significantly bolstered the global digital economy, fostering enhanced productivity, innovation, and trade. Utilizing panel data analysis, the study demonstrates that progress in ICT technology contributed approximately 0.33% to economic growth. Additionally, it facilitated an expansion of about 0.12% in product trade and 0.14% in service trade. The research also uncovered a “Diminishing Marginal Returns of ICT on Trade” effect, where trade volume increases with ICT development, but at a decelerating rate over time. To maximize trade growth potential, the study proposes increased governmental investment in ICT technology development and innovation, coupled with the establishment of digital trade standards. These measures could position digital trade as a catalyst for future economic expansion. While the research acknowledges limitations such as a restricted sample size and reliance on panel data, its conclusions offer valuable insights for policymakers and enterprises in emerging economies.First published online 2 July 2025